Teachers' Concerns About Implementing Instructional Supervision - Thomas-Hunte, Eartha (My University, 2015)
This phenomenological case study explored three teachers’ concerns about the implementation of instructional supervision/clinical supervision at a secondary school in the Victoria Education District in Trinidad. Data were collected through interviews and the use of the Concerns-Based Adoption Model. The findings revealed that the teachers had a conglomeration of concerns regarding self, task, and impact, with impact-collaboration concerns being the most predominant. Less intense or minimal concerns were noted in the areas relating to impact-consequence and refocusing, self-informational, and task management. All the participants suggested that, by understanding teachers’ concerns, more specific culturally and contextually relevant interventions pertinent to their actual needs could be provided in implementing a more collaborative instructional supervision approach for teaching and learning.
Keywords: Teacher attitudes; Secondary school teachers; Concerns; Teacher supervision; Instructional leadership; Case studies; Trinidad and Tobago